Effect of post–emergence herbicides on weed flora, growth and production efficiency of mungbean [Vigna radiata (L.) Wilczek] - Harshita Mishra; H.S. Kushwaha; Ajay Kumar Kashyap (Annals of Agricultural Research, 2023)
A field experiment was conducted at Mahatma Gandhi Chitrakoot Gramodaya Vishwavidyalaya, Chitrakoot, Satna (M.P.) during (kharif) rainy season in 2019-20 to 2020 -21 to study the effect of post-emergence herbicides on weed flora, growth and production efficiency of mungbean. The major monocot weed viz. Cynodon dactylon (25/m2 ) was found while, dominant dicot weeds were Parthenium hysterophorus (26/m2 ) and Convolvulus arvensis (18/ m2 ) at 45 days stage of crop. The significant lowest weed density and weed dry weight at 45 days stage were observed under fluazifop-p-butyl 13.4% W/W @ 250g/ha at 20-25 DAS (6.16 /m2 , 4.83 g/ m2 ) followed by aciflourfen sodium 16.5 % @ 140 g + clodinafop propargyl 8% @ 70g/ha at 20–25 DAS (7.02 /m2 , 5.44 g/m2 ). However, weed control efficiency was recorded higher under fluazifop-p-butyl13.4% W/W @ 250g/ha at 20-25 DAS (37.75%) at 45 days stage of crop. The weed index at the same stage was noted lowest under imazethapyr 10% SL @ 55g/ha at 20-25 DAS (3.40) followed by hand weeding (5.62). In weed control treatment, plant dry weight of greengram was noted significantly higher under fomesafen 11.1 % W/W @ 220 g + fluazifop-p-butyl 11.1 % W/W @ 220 g/ha at 20 – 25 DAS (31 g) and hand weeding at 20 and 40 DAS (31 g). Primary branches/plant was recorded numerically more in aciflourfen sodium 16.5 % @ 140 g + clodinafop propargyl 8 % @ 70 g/ha at 20 – 25 DAS (9.87) while, secondary and tertiary branches/ plant was found conspiously higher under fluazifop-p-butyl 13.4 % W/W @ 250 g/ha at 20 – 25 DAS (6.40; 3.87). Among the weed control plot, significantly superior grain yield, stover yield and biological yield (738 kg/ha, 3769 kg/ha and 4507 kg/ha) were recorded under imazethapyr 10% SL @ 55 g/ha at 20-25 DAS which exhibited statistically on par with weed free treatment. Harvest index (%) was numerically higher in fomesafen 11.1% @ 220 g + fluazifop-p-butyl 11.1% @ 220 g/ha at 20 – 25 DAS (19.98%) followed by aciflourfen sodium 16.5 % @ 140 g + clodinafop propargyl 8 % @ 70 g/ha at 20 – 25 DAS(18.36 %). Production efficiency was observed higher in imazethapyr 10% SL @ 55 g/ha at 20-25 DAS (8.2 kg/ day/ ha) followed by hand weeding (8.01 kg/day/ha).